Missing Meals and Missed Rides: Transportation Barriers to Food Access for Vulnerable Populations - Laura M. Keyes; Jintak Kim; Sowmya Balachandran; Sara Kuttler; Simon Andrew (Urban Science, 2025)
Food insecurity is not only shaped by behavioral, socioeconomic, and demographic factors but is also determined by an individual’s ability to access food in their community. Analyzing new survey data from a large city located in the southwest USA, this research adds to current dialogues on food insecurity among older adults and individuals with disabilities in economically disadvantaged communities. Using logistic regression, the findings provide nuanced evidence to distinguish between two crucial determinants of food insecurity related to transportation access—the lack of service availability and transportation unaffordability. One-third of respondents missed grocery trips due to a lack of affordable transportation. For individuals who cannot drive or do not own vehicles, access to ride services is critical to overcome exacerbated risks owing to food insecurity compared with those who own personal vehicles. Those relying on community-based ride services are more likely to miss grocery trips due to inadequate services. Our research further provides evidence that inadequate services result in greater food insecurity for specific vulnerable subgroups, such as those with poor health, renters, and those with lower incomes. Our findings highlight the importance of understanding behavioral travel constraints and call for equity-focused improvements in transportation systems to mitigate food access barriers.